Financing constraints, cash-flow risk, and corporate investment - Hirth, Stefan; Viswanatha, Marc (Journal of Corporate Finance, 2011)
Using an analytically tractable two-period model of a financially constrained firm, we derive an investment threshold that is U-shaped in cash holdings. We show analytically the relevant trade-offs leading to the U-shape: the firm balances financing costs for present and future investment, respectively. Our main argument is that financing costs today are more important than the risk of future financing costs. The empirically testable implications are that low-cash firms facing financing costs today are more reluctant to invest if they have less cash, or if their future cash flows are more risky. On the other hand, cash-rich firms facing no financing costs today invest in less favorable projects (i.e., forgo their real option to wait) if they have less cash, or if their future cash flows are more risky. The magnitude of these effects is amplified by the degree of market frictions that the firms are facing.